Manajemen Pengelolaan Unit Bisnis Bengkel Promatic sebagai Social Entreprise pada Lembaga Filantropi (Studi Kasus Institut Kemandirian Dompet Dhuafa) - Yulianti; Nadya Kharima (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
Social entrepreneurship is a very new thing in the field of entrepreneurship, in the concept of social entrepreneurship an institution tries to combine two aspects, namely social and profit. Establishment of a promatic workshop as an effort to institutional independence and as a space for updating automotive training after motorcycles as a place of training and work. The purpose of this study is to analyze the management carried out by the Dompet Dhuafa Independence Institute in the promatic workshop business unit as a social enterprise. The research method used is a qualitative descriptive research method with an approach to be able to analyze in detail and depth. Data collection techniques carried out by researchers using observation, interviews, and documentation studies. In analyzing the data, researchers tried to use data analysis techniques by Miles and Hubermen, namely by collecting data, coding data, and analyzing data. Then the theory used in this study as an analytical knife uses management theory put forward by George R. Terry with an emphasis on aspects of planning, organizing, implementing and controlling. The results of the study show that the Promatic workshop organized by the Independence Institute fits the main characteristics of a social enterprise. Then the four aspects of management were also carried out well to build the Mandiri Institute's confidence to open and manage new business units in other fields of education.